2020
DOI: 10.1128/aac.02103-19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Mutations That Partially Activate the Stringent Response Confer Multidrug Tolerance in Staphylococcus aureus

Abstract: Antibiotic tolerance is an underappreciated antibiotic escape strategy that is associated with recurrent and relapsing infections, as well as acting as a precursor to resistance. Tolerance describes the ability of a bacterial population to survive transient exposure to an otherwise lethal concentration of antibiotic without exhibiting an elevated MIC. It is detected in time-kill assays as a lower rate of killing than a susceptible strain and can be quantified by the metric minimum duration for killing (MDK). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 63 publications
4
31
1
Order By: Relevance
“…Accumulation of ppGpp results in massive transcriptional reprogramming of the cell, 176 and, most importantly, induces transient growth arrest 177–179 (this is the basis for the well‐established technique to isolate auxotrophic mutants using penicillin enrichment 180,181 ). Not surprisingly, the SR has been implicated in tolerance to CWA antibiotics in numerous studies with both Gram‐positive and ‐negative bacteria, 178,182–188 and in some cases, clinical mutants with enhanced tolerance due to background SR upregulation have been isolated 189 . In a particularly intriguing example, the ppGpp synthetases RelP and RelQ of S. aureus are induced by antibiotic exposure itself, resulting in high ampicillin and vancomycin tolerance 135 .…”
Section: Part II Mechanisms Of Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of ppGpp results in massive transcriptional reprogramming of the cell, 176 and, most importantly, induces transient growth arrest 177–179 (this is the basis for the well‐established technique to isolate auxotrophic mutants using penicillin enrichment 180,181 ). Not surprisingly, the SR has been implicated in tolerance to CWA antibiotics in numerous studies with both Gram‐positive and ‐negative bacteria, 178,182–188 and in some cases, clinical mutants with enhanced tolerance due to background SR upregulation have been isolated 189 . In a particularly intriguing example, the ppGpp synthetases RelP and RelQ of S. aureus are induced by antibiotic exposure itself, resulting in high ampicillin and vancomycin tolerance 135 .…”
Section: Part II Mechanisms Of Tolerancementioning
confidence: 99%
“…Not surprisingly, the SR has been implicated in tolerance to CWA antibiotics in numerous studies with both Gram‐positive and ‐negative bacteria, 178 , 182 , 183 , 184 , 185 , 186 , 187 , 188 and in some cases, clinical mutants with enhanced tolerance due to background SR upregulation have been isolated. 189 In a particularly intriguing example, the ppGpp synthetases RelP and RelQ of S. aureus are induced by antibiotic exposure itself, resulting in high ampicillin and vancomycin tolerance. 135 The more interesting question surrounding the SR and antibiotic tolerance, however, is whether or not growth arrest is the only effector of SR‐induced tolerance.…”
Section: Part II Mechanisms Of Tolerancementioning
confidence: 99%
“…In addition, (p)ppGpp conferred high level of beta lactam resistance in MRSA strains via increased expression of penicillin-binding proteins, encoded by mecA and pbpD [ 47 , 48 ]. Overproduction of (p)ppGpp due to rel mutations in clinical isolates resulted in increased tolerance to five different antibiotic classes [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the persister assays were performed under relaxed conditions, and thus, the role of (p)ppGpp might have been missed. Nevertheless, (p)ppGpp synthesis was previously shown to contribute to antibiotic tolerance in S. aureus (Geiger et al, 2014;Bryson et al, 2020) and other pathogens (Nguyen et al, 2011;Bernier et al, 2013). Nguyen et al (2011) suggested that in Pseudomonas aeruginosa, the stringent response contributes to antimicrobial tolerance in biofilms by reducing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%